If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = 29 + -3x Reorder the terms: 9 + 2x = 29 + -3x Solving 9 + 2x = 29 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 9 + 2x + 3x = 29 + -3x + 3x Combine like terms: 2x + 3x = 5x 9 + 5x = 29 + -3x + 3x Combine like terms: -3x + 3x = 0 9 + 5x = 29 + 0 9 + 5x = 29 Add '-9' to each side of the equation. 9 + -9 + 5x = 29 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 29 + -9 5x = 29 + -9 Combine like terms: 29 + -9 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 58-7x=29x+18 | | t^2-t+1=0 | | 4x+5=6x-7 | | x^2-5xy+4y^2=0 | | 3x*(-5xy)=a | | 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x | | 14x=-7 | | -35=5y | | -20=-5y | | 63=9y | | c^2=7c+18 | | -m^2-12=87 | | 4x+38=7x+20 | | X^2+4x^2+24x+24=4x^2+24x+36 | | 7+5a=8+2a | | 2x-3(x+6)=-4x(x-1) | | 7+7a+5a^2=8+2a+2a^2 | | 3y^2+10y=17y^2 | | -9x+4=2x+24 | | b^2+10b+9=0 | | 3(4x-1)=2(5x+4) | | 5x+7y=6 | | 6x-7=m | | 75-4x=32x+23 | | 3t-4=y | | (x+6)(x-2)=-7 | | V-3d=z | | 3x^2+4xy^2=1 | | 63-3x=6x+23 |